Strategies for improving the quality of education at SD Muhammadiyah Alam Surya Mentari in Surakarta - Anton Adi Suryo Kusuma; Naomi Fahma; Sutama Sutama; Budi Murtiyasa; Anam Sutopo (Himpunan Pengembang Kurikulum Indonesia, 2024)
This research is motivated by the demand for educational institutions to create quality human resources. Regulation of the Minister of National Education No. 63 of 2009 concerning the quality assurance system for education in Indonesia serves as a reference for regulating quality limits, quality assurance objectives, and quality level references. This study aims to improve the quality of education and identify its inhibiting factors at SD Muhammadiyah Alam Surya Mentari Surakarta. This research method is qualitative. Data collection was done by observation, interview, and documentation. The data validity technique uses source and method triangulation. The data analysis technique in this research has three stages: data reduction, data presentation, and conclusion drawing. The results showed that the strategies to improve the quality of education carried out by SD Muhammadiyah Alam Surya Mentari are: 1) Adopting four curricula, 2) Improving student achievement, both academic and non-academic, 3) Improving infrastructure facilities through a) minimum educator standards of S1, b) straightforward programs and division of tasks, c) adequate infrastructure, d) an environment that supports the learning process, e) foundation and community support. At the same time, the inhibiting factors are the large number of students and the lack of technology-based learning facilities in the classroom. Abstrak Penelitian ini dilatar belakangi adanya tuntutan bagi lembaga pendidikan untuk menciptakan sumber daya manusia yang berkualitas. Peraturan Menteri Pendidikan Nasional No 63 Tahun 2009 tentang sistem penjaminan mutu Pendidikan di Indonesia menjadi acuan dalam mengatur batasan mutu, tujuan penjaminan mutu dan acuan tingkatan mutu. Penelitian ini bertujuan untuk menganalisis strategi meningkatkan mutu pendidikan dan faktor penghambatnya di SD Muhammadiyah Alam Surya Mentari Surakarta. Metode penelitian ini ialah kualitatif. Pengumpulan data dilakukan dengan observasi, wawancara dan dokumentasi. Teknik keabsahan data menggunakan triangulasi sumber dan metode. Teknik analisis data dalam penelitian ini ada tiga tahapan, yaitu reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa strategi peningkatan mutu pendidikan yang dilakukan oleh SD Muhammadiyah Alam Surya Mentari yaitu: 1) Mengadopsi empat kurikulum, 2) Meningkatkan prestasi peserta didik baik akademik maupun non akademik, 3) Meningkatkan sarana prasarana melalui: a) standard pendidik minimal S1, b) program dan pembagian tugas yang jelas, c) sarana prasarana yang memadai, d) lingkungan yang mendukung proses pembelajaran, e) dukungan yayasan dan masyarakat. Sedangkan faktor penghambatnya yaitu jumlah peserta didik yang banyak dan minimnya fasilitas pembelajaran berbasis teknologi di kelas. Kata Kunci: Mutu pendidikan; sekolah dasar; strategi pendidikan